Romance motion verbs in language change: grammar, lexicon, discourse - Pfadenhauer, Katrin; Wiesinger, Evelyn (De Gruyter, 2024)
Cross-linguistically, motion verbs are frequently involved in language change and feature a wide array of motion-related constructions. The aim of this volume is to grasp more completely the typological characteristics and the developmental potential of motion verbs and to acknowledge the formal and functional diversity of motion-related constructions in Romance languages. To this end, the contributions in this collection provide synchronic and diachronic as well as typologically oriented studies that focus on motion verbs and single- and multi-verb constructions that have received scant attention to date. These include verbal periphrases, (pseudo-/semi-)copula and pseudo-coordinated constructions in Spanish, Italian, Romanian, French and French-based Creoles. In comparison to previous research on Romance languages, the present volume also adopts a broader perspective on language change, taking into account not only grammaticalization processes but also discursive, lexical and pragmatic phenomena such as the development of discursive, "ative or mirative functions. The studies build on functional, usage-based and constructionist models of language change and rely on corpus-based as well as experimental empirical approaches
Keywords: Aufsatzsammlung; Grammatikalisation; Verb; Romanische Sprachen